Validation of the Polish version of the EORTC QLQ‐CX24 module for the assessment of health‐related quality of life in women with cervical cancer. (19th August 2013) - Paradowska, D.; Tomaszewski, K.A.; Bałajewicz‐Nowak, M.; Bereza, K.; Tomaszewska, I.M.; Paradowski, J.; Pityński, K.; Skotnicki, P.; Greimel, E.R.; Bottomley, A.
<x xml:space="preserve">Abstract</x> The aim of our study was to undertake a prospective validation study of the Polish version of the EORTC cervical cancer (EORTC QLQ‐CX24) module used alongside the EORTC core measure. The translated module was pilot‐tested according to the established EORTC guidelines. Patients with histological confirmation of cervical cancer were eligible for the study. All patients filled out the Polish version of the EORTC QLQ‐CX24 module in addition to EORTC QLQ‐C30 and a demographic questionnaire. Standardised validity and reliability analyses were performed. One hundred and seventy‐one patients were enrolled into the study, mean age ± SD: 52.1 ± 9.6. Cronbach alpha coefficients, range 0.81–0.88, showed positive internal consistency. Re‐test was undertaken with 40 patients (23.4%). Interclass correlations for the EORTC QLQ‐CX24 ranged from 0.85 to 0.89 and proved appropriate test–retest reliability. Satisfactory convergent and discriminant validity in multi‐trait scaling analyses was seen. Concluding, the Polish version of the EORTC QLQ‐CX24 module is a reliable and valid tool for measuring HRQoL in patients with cervical cancer. It can be fully recommended for use in clinical and epidemiological settings in the Polish population.